Maculabatis ambigua sp. nov., a new whipray (Myliobatiformes: Dasyatidae) from the Western Indian Ocean - Last, Peter R.; Bogorodsky, Sergey V.; Alpermann, Tilman J. (Zootaxa, 2016)
A new whipray, Maculabatis ambigua sp. nov., described from material collected from the Red Sea and off Zanzibar (Tanzania), is probably more widespread in the northwestern Indian Ocean. It has been confused with other Indian Ocean whiprays of the genus Maculabatis (formerly Himantura in part) i.e. M. gerrardi and M. randalli. Maculabatis ambigua sp. nov. was first distinguished from these species by molecular analysis, and subsequently by a combination of morphological characters, i.e. disc shape, coloration, morphometrics and squamation. Molecular data suggest that it is most closely related to the morphologically similar M. gerrardi, which occurs further east in the Indian Ocean (Oman to Indonesia) and North-West Pacific (north to Taiwan). The dorsal disc of M. gerrardi typically has a full or partial coverage of white spots (usually present at least on the posterior disc), whereas M. ambigua sp. nov. is plain coloured. Maculabatis randalli, which occurs in the Persian and Arabian Gulfs, is plain coloured, but has a longer disc relative to its width, more acute and longer snout, longer head and larger intergill width, wider internasal distance, and a narrower secondary denticle band in adults. Maculabatis ambigua sp. nov. is relatively common in the shallow, soft-sedimentary habitats of the southern Red Sea from where it is taken as low-value or discarded bycatch of trawl fisheries. It is a medium-sized whipray with a maximum confirmed size of 840 mm disc width.